2003
DOI: 10.1080/00222890309603158
|View full text |Cite
|
Sign up to set email alerts
|

Saccade-Stepping Interactions Revise the Motor Plan for Obstacle Avoidance

Abstract: The authors used a stimulus-response compatibility paradigm to assess the effect of changing the estimated time to obstacle contact. A limb-selection cue was presented in different phases of gait to young (n = 5) and to older (n = 4) adults while they were moving toward a foam obstacle in the walking path. A downward saccade was initiated after the cue; the saccade typically occurred during the stance phase of the target limb (the foot cued to lead the step over the obstacle). The mean saccade-step latency aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 36 publications
6
30
0
Order By: Relevance
“…Re-direction of visual Wxation was made to the landing area in compensatory stepping reactions following platform translation as well (Zettel et al 2005), albeit infrequent, and Patla and Vickers (1997) have shown when the ART is long information regarding the obstacle is acquired in the steps before crossing but peripheral vision of the obstacle and crossing limb is suYcient to perform the task: Wxations are directed to the landing area during the cross-over step. This has been supported more recently by Di Fabio et al (2003a). Interestingly, in a later study with older adults Di Fabio et al (2005) reported a reduction in the frequency of down saccades in high-risk cognitively challenged older adults initiating obstacle step-over.…”
Section: Bfisupporting
confidence: 52%
See 2 more Smart Citations
“…Re-direction of visual Wxation was made to the landing area in compensatory stepping reactions following platform translation as well (Zettel et al 2005), albeit infrequent, and Patla and Vickers (1997) have shown when the ART is long information regarding the obstacle is acquired in the steps before crossing but peripheral vision of the obstacle and crossing limb is suYcient to perform the task: Wxations are directed to the landing area during the cross-over step. This has been supported more recently by Di Fabio et al (2003a). Interestingly, in a later study with older adults Di Fabio et al (2005) reported a reduction in the frequency of down saccades in high-risk cognitively challenged older adults initiating obstacle step-over.…”
Section: Bfisupporting
confidence: 52%
“…Di Fabio et al (2003b) argue stepping movements use this visual anchoring behavior, proposed by Johansson et al (2001) for object manipulation, and hence saccadic eye movements are linked to stepping. Studies on obstacle avoidance suggest that visual input is utilized during the approach phase, which is evident from visual Wxations directed to the obstacle (Patla and Vickers 1997) or downward saccades made to an area behind the obstacle following a cue as to which limb to initiate the step over the obstacle (Di Fabio et al 2003a). However, peripheral vision is suYcient while stepping over the obstacle as Wxation is directed to the landing area (Patla and Vickers 1997) or upward saccades are made to adjust gaze to a forward looking direction (Di Fabio et al 2003a) and not the obstacle during the cross-over phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al [34] showed that the resolution of attention was better in the lower versus upper visual field (measured by a greater percentage of correct responses). Their findings could not be due to a neuroanatomical infrastructure since functional magnetic resonance imaging shows roughly equal representations of the upper and lower visual fields in the primary motor cortex [34].…”
Section: Discussionmentioning
confidence: 99%
“…The requirement to step over an obstacle once the visual stimulus location was detected facilitated a down-saccade prior to initiating the step. The 'saccade-stepping' sequence has been observed previously in both young and elderly people and is a component of a feedforward motor program that controls stepping behaviors [34,48]. It is important to note that the down-saccade after the stimulus had been extinguished was acceptable and was used as a 'limb-independent' measure of RT that signaled the onset of a stepping motor program (see the statistical analysis).…”
Section: Experiments Nomentioning
confidence: 99%